Tourism in Pachacámac and their contributions to the community - García Chumioque, Florisa G. (2016)
Pachacámac district is recognized by the Archaeological Sanctuary of the same name and selling chicharrones in the district, however, this district has many tourist resources of interest to experiential tourism, rural tourism, gastronomic tourism, religious tourism.This research sought to make a diagnosis on the benefits that tourism is generating in the district of Pachacamac. The objectives that guided this research are to estimate the tourism villager attitude Pachacámac determine the role of local government, identify the bodies that manage tourism, know the benefits they generate for the villager tourism.The methodology used was quantitative and descriptive. interviews were conducted with a representative of the Municipality of Pachacamac, the pastor of the First Church of Pachacamac and the survey addressed to the villager and workers in the tourism and hotel business, which made up the population and sample.To analyze the perception of the villager on the benefits of tourism in it 247 surveys were conducted to settler where it was concluded: two less known tourist and visited places are those that offer the "agritourism" as is the Fundo Marengo and Bioagricultura White House. Bioagricultura White House Biohuerto Santa Maria, Chapel Virgen de Lourdes, Heladería: Among the results obtained in the investigation the tourist inventory District Pachacámac determined necessary to make a diferent proposal of the tourism product to be developed giving priority to the following tourist resources developed White House, Lomas de Lúcumo, Holy Saviour Church.Referring to the study population was obtained resources visited by them are the Sugar Loaf Mountain, where lies the Stone of Love and the Fountain of Youth, located in the Town Rural Cardal Center, this could be due to admission is free. People perceive that tourism is very important and they cater well to the visitor.The Church and the Municipality of Pachacamac are interested in supporting the development of tourism Pachacámac and revalues the fervor of religious holidays of the people. Sector entrepreneurs 68% have no studies of tourism, hospitality and gastronomy this being a weakness.